Lithic industries, territory and mobility in the western Linear Pottery Culture - Allard, Pierre; Denis, Solène (Journal of Lithic Studies, 2021)
Territory is a complex notion whose definition varies depending on the discipline in which it is applied. Research on the notion of territory has often focused on the Palaeolithic. Studies in this field are mainly based on comparisons between archaeological assemblages and ethnographic data, an approach originating from the work of L.R. Binford, who introduced the concept of mobility, leading to various models of spatial occupation. How have researchers approached the notion of territory with regard to the first mixed farming populations of the Linear Pottery Culture in the Seine Basin and neighbouring regions? Can lithic industries contribute to our understanding of how these first sedentary populations perceived their territory? In this paper, we show that these first Neolithic communities likely obtained their siliceous materials via direct procurement strategies across a territory that they knew well and regularly frequented. In our study area, centred around the Rhine-Meuse region and the Seine Basin, two distinct litho-spaces are comprised of: 1) small numbers of minor territories with local resources, and 2) vast territories requiring greater mobility among the groups that occupied them. Furthermore, the procurement strategies of the occupants of the regions with few siliceous resources seem to have been based on long-distance relationships and networks. In this case, a high degree of mobility and ensuing social relations would have contributed to the attractivity of villages.